Родинне дерево Степана Смаль-Стоцького - Dobrzhanskyi, Oleksandr; Tsmukh, Piter (Чернівецький національний університет імені Юрія Федьковича, 2021)
Abstract. This work is dedicated to the study of the family history of famous scientist and public figure, academician-founder of the Ukrainian Academy of Sciences Stepan Smal-Stotsky. The authors noted that its roots can be traced only from the second half of the 18th century, because there are no more ancient metric books on his native village of Nemyliv. The scientist's parents were middle-class peasants. His paternal grandparents played an important role in his upbringing. The focus of the article is paid to the development of families after S. Smal-Stotsky married Emilia from the Zarevych family. Her father was a priest in the village of Rozhniv in Galicia. Stepan and Emilia Smal-Stotsky had three children. Daughter Iryna, and 2 sons, Roman and Nestor. Their fate was different. They were all successful, but each in his own way. Roman Smal-Stotski continued his father's business, was a famous politician and philologist. But all his life he was alone, without establishing a family. Daughter Iryna became a reliable assistant and support of her husband Ostap Lutskyi, who was an extraordinary person, an original poet, a prominent figure in the cooperative movement, a member of the Polish Sejm and Senate. His fate was tragic after the arrival of the Bolsheviks in Western Ukraine. He was arrested and died in the Gulag camps. To a large extent, S. Smal-Stotskyi's grandson Yuri Lutsky, well known as a literary critic, Slavic scholar, author of many interesting research studies, as well as family memoirs, followed in his grandfather's footsteps. Born in 1919 in Galicia, he studied at the Universities of Berlin and Birmingham, and served in the British Army. After World War II, he moved to Canada. He had taught at the Universities of Toronto and Saskatchewan. His youngest daughter Khrystyna (great-granddaughter of S. Smal-Stotskyi) is a professor of English philology. She named her son Stepan in honor of her great-grandfather. The least information is available about Nestor Smal-Stockyi, who first lived in Italy and then in Peru. His son and grandsons became civil engineers and kept the surname Smal-Stotskyi. As we can see, none of S. Smal-Stotskyi's children was able to stay in Ukraine. World wars scattered them on different continents. But their descendants remember S. Smal-Stotsky, they are proud of him, as evidenced by their messages on social networks, letters, published memoirs.
THE FAMILY TREE OF STEPAN SMAL-STOTSKY
Keywords: Smal-Stotskyi's family; Iryna, Roman and Nestor Smal-Stotskyi; Ostap and Yurii Lutskyi.